Mechanisms of interaction of the N-acetyl-p-aminophenol metabolites in terms of nephrotoxicity. (April 2015) - Ściskalska, Milena; Śliwińska-Mossoń, Mariola; Podawacz, Magdalena; Sajewicz, Waldemar; Milnerowicz, Halina
Abstract Context: Epidemiological studies have demonstrated that chronic use of N-acetyl-p-aminophenol is correlated with the occurrence of renal dysfunction. Objective: Aim of this study was to review the literature on the mechanisms of interaction N-acetyl-p-aminophenol metabolites in terms of nephrotoxicity. Methods: We present a literature review of studies published in English language on the damage effects of N-acetyl-p-aminophenol on the kidneys, accessed through PubMed database. Results: The pathogenesis of drug-induced nephrotoxicity attributed to the action of cytochrome P450 enzymes, prostaglandin endoperoxide synthase (PGES) and N-deacetylase. The metabolism of N-acetyl-p-aminophenol with the participation of PGES more explicit is in the core of kidney, whereas cytochrome P450 enzymes play role in the renal cortex. Due to the action of cytochrome P450 and N-deacetylase, a very reactive N-acetyl-p-benzochinoimine (NAPQI) is formed. The result of the catalytic activity of PGES is p-benzoquinone (PBQI) production. The formation of NAPQI and PBQI is accompanied by the production of free radicals. Metabolites can connect covalently with sulfhydryl groups of renal proteins, what can cause the injury of proximal tubules. N-acetyl-p-aminophenol may initiate the apoptosis process involving activation of caspase-9 and caspase-3, but also caspase-12 as a result of generation of free radicals. Conclusions: The process of NAPQI and PBQI formation can increase oxidative stress that promotes the kidneys damage. The ability of metabolites to produce covalent bonds with sulfhydryl groups of proteins can increase the nephrotoxicity. It was assumed that the induction of apoptosis in renal tubular epithelial cells, and not necrosis underlies the nephrotoxic potential of N-acetyl-p-aminophenol.